10 kHz spinal cord stimulation for the treatment of chronic back and/or leg pain: Summary of clinical studies. (August 2020) - Luecke, Thorsten; Edgar, Deborah; Huse, Daniel
Chronic pain has a major impact on sufferers and their families. The associated health care costs are substantial. In the context of increasing prevalence, effective treatment options are ever more important. 10 kHz spinal cord stimulation has been shown to effectively provide pain relief, aid in opioid reduction, and improve quality of life in patients with chronic intractable pain. The present review aims to summarize the clinical evidence related to the use of 10 kHz SCS in chronic back and/or leg pain. We searched the PubMed database between 2009 and 2 June 2020 for articles reporting clinical studies that included at least 10 human subjects permanently treated with a 10 kHz SCS system (Senza ® system) for chronic back and/or leg pain for a minimum of 3 months. A randomized controlled trial (SENZA-RCT), as well as several prospective and retrospective studies, reported clinical outcomes in subjects with chronic back and leg pain treated with 10 kHz SCS. A high proportion of subjects (60%–80%) reported long-term response to therapy. Pain relief was provided without paresthesia. Other studies showed promising pain relief outcomes in subjects with back pain ineligible for spinal surgery, neuropathic limb pain, and in those with previously failed traditional low-frequency SCS. Most studies reported improved quality of life metrics and/or reduced opioid intake. Level 1 evidence has already been established for the use of 10 kHz SCS in treating chronic back and leg pain, corroborated by real-world, clinical experience. Exploratory studies also show the potential of the therapy in other refractory pain syndromes, although larger studies are desired to validate their findings. Overall, the literature suggests that 10 kHz SCS provides long-term pain relief in a high proportion of patients, along with improved quality of life and reduced opioid consumption.